On a syntactically defined invariant of symbolic dynamics - Krieger, Wolfgang (Ergodic theory and dynamical systems, 2000)
A partially ordered set that is invariantly associated to a subshift is constructed. A property of subshifts, also an invariant of topological conjugacy, is described. If this property is present in a subshift then the constructed partially ordered set is a partially ordered semigroup (with zero). In the description of these invariants the notion of context is instrumental.
Erscheinungsvermerk laut Verlagsseite Vol. 20(2000) Issue 2, laut PDF jedoch Vol. 19(1999)
Gesehen am 15.06.2018